The Optimum Reaction Time, Activation Energy and Frequency Factor of Methyl Ricinoleate Nitration - Abdullah Abdullah; Triyono Triyono; Wega Trisunaryanti; Winarto Haryadi (Indonesian Journal of Chemistry, 2013)
Determination of the optimum reaction time, activation energy (Ea) and frequency factor (A) of methyl ricinoleate nitration has been done. The nitration was conducted with the mole ratio of methyl ricinoleate to HNO3 of 1:15. The reaction was conducted at temperatures of 29 and 64 °C with a variation of reaction time for 10, 20, 30, 60, 90, 120, and 150 min. Determination of activation energy and frequency factor was performed in a temperature of 29, 33, 38, 44, 49, 57 and 64 °C. The results showed that the optimum reaction time is 90 min. The activation energy (Ea) and frequency factor (A) was 44.5 kJ/mol and 4.780 x 103 sec-1, respectively.